Neke karakteristike notacijskih shema - Tkalac, Slavko (Array, 1996)
The paper gives a short review of fundamental knowledge repesentation methods: logical, graphical, structured and procedural notational schemes. Special care is given to notational schemes, classifications and characteristics on which classifications were done.